La Révolte de Bû Ziyân en Algérie, 1849 - Julia Clancy-Smith (Revue des Mondes Musulmans et de la Méditerranée)
This study takes the 1849 revolt led by Bû Ziyân, a Mahdist « pretender », as a socio-cultural site for exploring rural popular mobilization under the ideological banner of the Muslim redeemer during the French conquest in Algeria. Utilizing a micro-historical methodology to examine the movement of protest on the Sahara's rim, the article raises the following questions : How were the socially understood and constructed paradigms of « saint/wali/murabit »implicated in the « model »or notion of the Muslim savior ? To what degree did local Sufi shaykhs or leaders act to promote or to dampen the revolutionnary potential of the mahdi ? What can this short-lived, if spectacular rebellion, tell us about the collective attitudes of ordinary people toward the mahdi ? And finally, what does this revolt in a small oasis reveal about collective memory - about the intersections between oral culture/traditions, rumors and written texts concerning the advent of the mahdi ? By way of conclusion, the author argues that the bloody repression of Bû Ziyân's revolt by the French army convinced religious notables, including Sufi elites, to search for accomodation with the colonial regime as early as 1850.